Air‐cored axial flux permanent magnet generator for direct driven micro wind turbines - Tareq S. El‐Hasan (IET Renewable Power Generation, 2023)
Abstract This paper presents the development of an Air‐Cored Axial Flux Permanent Magnet Generator (ACAF PMG) integrated for direct battery charging scheme for urban and rural micro‐wind turbine applications rated at 1 kW. The proposed generator has a Single Stator Double Rotor configuration with a relatively short axial length. In this paper, the analytical model for generator sizing is presented and the main parameters are defined. Novel analytical model is presented to determine the required number of turns for each phase in order to produce a balanced voltage in the three phases. The generator is electromagnetically analyzed using Finite Element model and simulated using Matlab/Simulink to predict its performance under several operating conditions. The effect of retainment ring type on the generator performance is also demonstrated. The machine is harnessed to a battery bank via a three‐phase fully controlled converter using six bridge thyristors to regulate the output voltage delivered from the generator to the battery. Generator model and simulation results are validated via experimental tests. The preliminary experimental results showed a good match with the simulation results. Moreover, the proposed machine is compared favourably with other counter machines of similar configuration and power ratings in terms of machine size, power‐to‐weight ratio, and voltage regulation. This paper therefore demonstrates the concrete benefits of utilizing the axial flux PMG in scavenging energy to generate electrical power from micro wind turbines.